The turtle who fell of the stick - N/A (Salangor : Mind to mind .)
The Turtle Who Fell Off the Stick is a story about a turtle who talks during a flight with her swan friends and falls because she doesn$1 (Bt follow their advice. Moral: Think before you speak.s
Keywords: English - Book